The Impact of Artificial Intelligence on Current Social Employment and Structure: Empirical Evidence from Provincial Industrial Robots - Zhang, Yu; Chen, Ruizhi; Huang, Jing (International Journal of Global Economics and Management, 2024)
Artificial intelligence, as the core driving force of the new round of technological revolution and industrial change, has far-reaching impact on current social employment and structure. This study, based on the data of provincial industrial robots, explores the impact of artificial intelligence on employment. Through literature review, it is found that artificial intelligence has impact on the labor market, which may lead to changes in employment scale, employment structure, and income distribution. The study uses panel data model to analyze the impact of artificial intelligence development on employment scale and structure in 31 provinces (autonomous regions, municipalities directly under the Central Government) of China from 2010 to 2019. The results show that the development of artificial intelligence has a significant promoting effect on the employment scale in China, and also affects the employment structure towards “high-end” direction, but there is also a spillover effect towards “polarization”. In addition, the study finds that artificial intelligence has different effects on the employment of labor with different skills, promoting the employment of high-skilled labor in the manufacturing industry and inhibiting the employment of low-skilled labor, leading to a trend of high-end employment structure in the manufacturing industry. Therefore, the study proposes some prospects and suggestions for the impact of artificial intelligence on the social employment structure, in order to promote the transformation and upgrading of the industry, and achieve efficient intelligent production and optimal adjustment of employment structure. Through in-depth analysis of this study, important reference basis is provided for the current social issues facing the impact of artificial intelligence.